2015
DOI: 10.17492/manthan.v2i1.6434
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater Arsenic Contamination in Bihar: Causes, Issues and Challenges

Abstract: Around forty percent of the district of Bihar is having arsenic in its groundwater. The causes of arsenic contamination are mostly through geogenic channel. Excess use of arsenic in drinking water over prolonged period leads to primary, secondary and tertiary health impacts. The agricultural activity is getting hampered due to decline in soil fertility, productivity, and, nuisance of food chain problem. Social problems like depression, suicidal tendency and social ignorance are common, and, therefore, hinder t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Numerous studies have revealed that arsenic contamination in groundwater has been reported in several Indian states, and the problem is getting worse. The Arsenic threat is prominent among people living in the Himalayan river belt including Bihar and West Bengal [13]. Arsenic exposure causes many diseases including cancer, renal failure and diabetes [14].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have revealed that arsenic contamination in groundwater has been reported in several Indian states, and the problem is getting worse. The Arsenic threat is prominent among people living in the Himalayan river belt including Bihar and West Bengal [13]. Arsenic exposure causes many diseases including cancer, renal failure and diabetes [14].…”
Section: Discussionmentioning
confidence: 99%
“…Further, younger cancer patients may face life disruptions (Clark & Fasciano 2015;Nass et al 2015) such as career/education, future plans, trust in health, financial burdens, peer relationships, and family dynamics. In addition, their geographical establishment could be held responsible, since most of the inhabitants of arsenic-affected middle Gangetic plain of Bihar, for obvious reasons, could not relocate (Bhardwaj et al 2019) and as such are bound to live under continuous apprehension for their next generations, highly vulnerable to several arsenic-induced diseases (Laskar et al 2010;Syed et al 2012;Thakur & Gupta 2015;Suman et al 2020). Most of the AIC patients of the age group 32-40 years were literate (63.63%).…”
Section: Discussionmentioning
confidence: 99%
“…This study intends to contribute towards existing literature and provide comprehensive evidence on the effect of arsenic poisoning on health as well as socio-economic aspects in Bangladesh. Several authors have tried to analyse the severe health implications of arsenic poisoning across various states in India like Bihar (Singh & Ghosh, 2012; Thakur & Gupta, 2015; Kumar et al, 2021). Unlike previous studies with epidemiological focus, this study uses large nationally representative dataset and rigorous empirical techniques so as to examine the health implications of arsenic poisoning.…”
Section: Introductionmentioning
confidence: 99%